The problem with petrous? A consideration of the potential biases in the utilization of pars petrosa for ancient DNA analysis. Issue 4 (8th August 2019) - Charlton, Sophy; Booth, Thomas; Barnes, Ian
ABSTRACT: Advances in NGS sequencing technologies, improved laboratory protocols and new bioinformatic workflows have seen huge increases in ancient DNA (aDNA) research on archaeological materials. A large proportion of aDNA work now utilizes the petrous portion of the temporal bone ( pars petrosa), which is recognized as an excellent skeletal element for long-term ancient endogenous (host) DNA survival. This has been significant due to the often low endogenous content of other skeletal elements, meaning that large amounts of sequencing are frequently required to obtain sufficient genetic coverage. However, exclusive sampling of the petrous for aDNA analysis introduces a new set of potential biases into our scientific studies – and these issues are yet to be considered by ancient DNA researchers. This paper aims to outline the possible biases of utilizing petrous bones to undertake aDNA analyses and highlight how these complications may potentially be overcome in future research.